HUBUNGAN IMT, LINGKAR PERUT, KONSUMSI MAKANAN ASIN, DAN KONSUMSI BUAH SERTA SAYUR DENGAN KEJADIAN HIPERTENSI PADA KELOMPOK DEWASA JAWA BARAT USIA 26-45 TAHUN (ANALISIS DATA RISKESDAS 2018) - Andi Ummu Aulia Ainundini Tenrigangka (2021)
Hypertension is a state of systolic blood pressure 140 mmHg or diastolic blood pressure 90 mmHg. Untreated hypertension leads to cardiovascular disease such as stroke, heart failure, coronary heart disease, even death. West Java is the second highest province of hypertension in Indonesia. Aim of the study was to determine the relationship between BMI, waist circumference, salty food, fruit, and vegetable consumption with hypertension in West Javanese adult aged 26-45 years based on the analysis of Riskesdas 2018. This study was an observational analytic study with a cross-sectional design, and uses secondary data from Riskesdas 2018. There was 11.616 samples. Results states there were 39% of respondents had hypertension, 47% had a normal BMI, 45% had central obesity, 56% often ate salty foods, 77% ate less fruit, and 92% of respondents ate less vegetables. There were relationship between nutritional status based on BMI (p = 0.000), nutritional status based on abdominal circumference measurement (p = 0.000), salty foods consumption pattern (p = 0.026), and fruit consumption pattern (p = 0.004) with the incidence of hypertension. There was no relationship between vegetable consumption pattern (p = 0.724) with the incidence of hypertension.